An Agostic Iridium Pincer Complex as a Highly Efficient and Selective Catalyst for Monoisomerization of 1‐Alkenes to trans‐2‐Alkenes. Issue 6 (2nd January 2017) - Wang, Yulei; Qin, Chuan; Jia, Xiangqing; Leng, Xuebing; Huang, Zheng
Abstract: A unique Ir complex ( tBu NC C P)Ir with the pyridine–phosphine pincer as the sole ligand, featuring a dual agostic interaction between the Ir and two σ C−H bonds from a t Bu substituent, has been prepared. This complex exhibits exceptionally high activity and excellent regio‐ and stereoselectivity for monoisomerization of 1‐alkenes to trans ‐2‐alkenes with wide functional‐group tolerance. Reactions can be performed in neat reactant on a more than 100 gram scale using 0.005 mol % catalyst loadings with turnover numbers up to 19000. Abstract : An agostic pincer iridium complex is extremely efficient for isomerization of various terminal alkenes, including very challenging linear α‐olefins, to trans ‐2‐alkenes with high positional and stereochemical selectivity.